The Effect of Using Active Knowledge Sharing Strategy on Reading Comprehension - Wael, Ahmad; Saputra, Dian; Kamaluddin, Kamaluddin (Universitas Muhammadiyah Sorong, 2023)
The writers formulate the problem statement which is there any significant effect of using Active Knowledge Sharing strategy on students’ Reading comprehension of the eleven grade students at SMK Negeri 2 Kota Sorong. This study is quantitative research and the study use classroom action methodology. the instrument of this study are Pre-test. This study take place at SMK Negeri 2 Kota Sorong.The result of the study could improve 15 students in reading comprehension at eleven grade pariwisata SMK Negeri 2 Kota Sorong. It was shown by the result of pre-test 42,27 and the result of post-test 1 was 60,53 and post-test 2 was 84,67. From the data above, the effect of active knowledge strategy can improve students’ reading comprehension in reading a narrative text and students’ attention, participation, and in learning especially eleven grade pariwisata SMK Negeri 2 Kota Sorong 2019/2020 academic year